KSHV RTA antagonizes SMC5/6 complex-induced viral chromatin compaction by hijacking the ubiquitin-proteasome system - Han, Chunyan; Zhang, Dun; Gui, Chenwu; Huang, Liang; Chang, Sijia; Dong, Lianghui; Bai, Lei; Wu, Shuwen; Lan, Ke (PLoS pathogens, 2022)
Kaposi’s sarcoma-associated herpesvirus (KSHV) is a double-stranded DNA virus with the capacity to establish life-long latent infection. During latent infection, the viral genome persists as a circular episome that associates with cellular histones and exists as a nonintegrated minichromosome in the nucleus of infected cells. Chromatin structure and epigenetic programming are required for the proper control of viral gene expression and stable maintenance of viral DNA. However, there is still limited knowledge regarding how the host regulates the chromatin structure and maintenance of episomal DNA. Here, we found that the cellular protein structural maintenance of chromosome (SMC) complex SMC5/6 recognizes and associates with the KSHV genome to inhibit its replication. The SMC5/6 complex can bind to the KSHV genome and suppress KSHV gene transcription by condensing the viral chromatin and creating a repressive chromatin structure. Correspondingly, KSHV employs an antagonistic strategy by utilizing the viral protein RTA to degrade the SMC5/6 complex and antagonize the inhibitory effect of this complex on viral gene transcription. Interestingly, this antagonistic mechanism of RTA is evolutionarily conserved among γ-herpesviruses. Our work suggests that the SMC5/6 complex is a new host factor that restricts KSHV replication.